2014
DOI: 10.1007/s00268-014-2598-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Pulmonary Artery during Video‐Assisted Thoracoscopic Left Upper Lobectomy

Abstract: This new technique offers shorter surgical and postoperative drainage time, shorter hospital stays, and fewer complications than conventional c-VATS upper left lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In MP VATS, an upper lobectomy was usually challenging during the dissection along the truncus anterior branch of the pulmonary artery; the iatrogenic injury would lead to major bleeding and subsequent manipulation was technically demanding during the operation [18]. However, in SP VATS lobectomy, the mobilization of the apical branch was switched as the first step.…”
Section: Discussionmentioning
confidence: 99%
“…In MP VATS, an upper lobectomy was usually challenging during the dissection along the truncus anterior branch of the pulmonary artery; the iatrogenic injury would lead to major bleeding and subsequent manipulation was technically demanding during the operation [18]. However, in SP VATS lobectomy, the mobilization of the apical branch was switched as the first step.…”
Section: Discussionmentioning
confidence: 99%
“…Those reports indicate the need for some change of operative procedure, one of which means that the LSPV stump should be as short as possible. Regarding operative procedure, Guo et al reported the modified method of VATS left upper lobectomy, which offers favorable clinical outcome compared with conventional VATS left upper lobectomy [9]. Considering other factors, development of atrial fibrillation which is frequently observed after left lobectomy may also have an impact on thrombus formation.…”
Section: Discussionmentioning
confidence: 96%
“…Subgroup analysis showed that most conversions to open surgery occurred in left upper lobectomy due to pulmonary artery hemorrhage and dense lymph nodes surrounding the blood vessels. Other studies have shown that dissection along the truncus anterior branch of the pulmonary trunk during upper lobectomy is often challenging and prone to severe bleeding that is difficult to manage 13,29,30 . Because the position of the bronchus is relatively fixed and is often surrounded by lymph nodes, the motion of the hilum increases after priority severing of the left upper lobe bronchus.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that dissection along the truncus anterior branch of the pulmonary trunk during upper lobectomy is often challenging and prone to severe bleeding that is difficult to manage. 13 , 29 , 30 Because the position of the bronchus is relatively fixed and is often surrounded by lymph nodes, the motion of the hilum increases after priority severing of the left upper lobe bronchus. Reduced bronchial and lymph node obstructions make it safer to dissect the pulmonary vessels and apply a stapler, with a lower conversion rate to thoracotomy.…”
Section: Discussionmentioning
confidence: 99%